Implementasi Program CSR dalam Menguatkan Citra PT SIER - Nurkholis, Dio; Prayogi, Audya Nisa; Kurniawan, Anto (Journal Of Human And Education (JAHE), 2024)
This study aims to determine the role of Public Relations of PT SIER in implementing CSR programs in accordance with the existing vision and mission, and whether the programs run are in accordance with GCG and grouped into CSR Community Development, Sustainable Development and profit groups, and to find out that the programs run can improve the image of PT SIER. In addition, the author also wants to know the strategies and programs run by TJSL or PR to strengthen and maintain the image of PT SIER Surabaya. This study uses a qualitative descriptive research method, which focuses on research with data collection techniques using In Depth Interviews. The results of the study indicate that PT SIER has implemented CSR programs well and in a structured manner, in accordance with GCG principles. The CSR program run by PT SIER also has a positive impact on the company's image. Keywords: Public Relations, CSR, Corporate Image, GCG, Community Development, Sustainable Development